Ambidextrous employees and sustainable innovation practices - empirical validation of structural linkage. (8th February 2023) - Singh, Nikita; Singh, Vinay; Patwadhan, Manoj; Upadhyay, Yogesh
Present study: 1) focuses on establishing the structural relationship between exploratory and exploitative behaviour of ambidextrous employees working in innovation-based organisations in India; 2) attempts to link the ambidextrous behaviour of employees with sustainable innovative practices of these organisations. A theoretical model was proposed and for its empirical verification, primary data was collected from 200 innovative organisations across India. The data were analysed using statistical methods namely, EFA, CFA, and structured equation model (SEM). All the proposed hypotheses show significant statistical support, and thus it is concluded that the organisational and technological sustainable innovative practices are positively influenced by employees' ambidextrous behaviour. The study contributes to a novel set of theories on the interdependence of employees' ambidextrous behaviour fostering sustainable innovation practices of the organisations, in their unique way.